The effect of different shape and perforated rHDPE in concrete structures on flexural strength - Yaakob, Mohd Yuhazri; K. M., Hafiz; YZA, Myia; Jia, C. P.; Haeryip, Sihombing; Salit, Mohd Sapuan; Badarulzaman, Nur Azam (IOP Sciences, 2017)
This research was carried out to develop a reinforcing structure from recycled HDPE plastic lubricant containers to be embedded in concrete structure. Different forms and shapes of recycled HDPE plastic are designed as reinforcement incorporate with cement. In this study, the reinforcing structure was prepared by washing, cutting, dimensioning and joining of the waste HDPE containers (direct technique without treatment on plastic surface). Then, the rHDPE reinforced concrete was produced by casting based on standard of procedure in civil engineering technique. Eight different shapes of rHDPE in concrete structure were used to determine the concrete's ability in terms of flexural strength. Embedded round shape in solid and perforated of rHDPE in concrete system drastically improved flexural strength at 17.78 % and 13.79 %. The result would seem that the concrete with reinforcing rHDPE structure exhibits a more gradual or flexible properties than concrete beams without reinforcement that has the properties of fragile.